Pengaruh Return On Assets (Roa) Dan Return On Equity (Roe) Terhadap Capital Adequacy Ratio ( Car) Pada PT. Bank Danamon Indonesia Tbk - Yeyen Rara Bafah; Puji Muniarty (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Timor, 2022)
This study aims to analyze the effect of return on assets (ROA) and return on equity (ROE) on the capital adequacy ratio (CAR) at PT. Bank Danamon Indonesia Tbk. The type of associative research with a quantitative and population approach in this study is in the form of balance sheet and income statements from 2006 – 2020 (15 years) from PT Bank Danamon Indonesia Tbk. The sample in this study is 12 years from the period 2009 – 2020. The data collection method is documentation and literature study using purposive sampling. Data analysis in this study used the classical assumption test, multiple linear regression, t test, f test and the coefficient of determination. The results show that the Return On Assets (ROA) has a partially significant effect on the Capital Adequacy Ratio (CAR) at PT. Bank Danamon Indonesia Tbk. Return On Equity (ROE) does not have a significant effect partially on the Capital Adequacy Ratio (CAR) at PT. Bank Danamon Indonesia Tbk. Return On Assets (ROA) and Return On Equity (ROE) have a significant effect simultaneously on the Capital Adequacy Ratio (CAR) at PT. Bank Danamon Indonesia Tbk.